2019
DOI: 10.3847/1538-4357/ab2b49
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Type Ia Supernova 2014J for Nearly 900 Days and Constraints on Its Progenitor System

Abstract: We present extensive ground-based and Hubble Space T elescope (HST ) photometry of the highly reddened, very nearby type Ia supernova (SN Ia) 2014J in M82, covering the phases from 9 days before to about 900 days after the B-band maximum. SN 2014J is similar to other normal SNe Ia near the maximum light, but it shows flux excess in the B band in the early nebular phase. This excess flux emission can be due to light scattering by some structures of circumstellar materials located at a few 10 17 cm, consistent w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 138 publications
(145 reference statements)
4
8
0
Order By: Relevance
“…The parameters that define reference sets are shown in Table 2. The CSM parameters of these characteristic sets are consistent with the fitting results in Wang et al (2019) and Li et al (2019), where the likely distances to the CSM around a few high-velocity SNe Ia were found to be approximately (1 ∼ 2) × 10 17 cm. The optical depths were found to be around 0.7 for the axisymmetric disk model, and 0.15 for the spherical shell and axisymmetric shell model.…”
Section: Kernel Of Intensitysupporting
confidence: 86%
See 1 more Smart Citation
“…The parameters that define reference sets are shown in Table 2. The CSM parameters of these characteristic sets are consistent with the fitting results in Wang et al (2019) and Li et al (2019), where the likely distances to the CSM around a few high-velocity SNe Ia were found to be approximately (1 ∼ 2) × 10 17 cm. The optical depths were found to be around 0.7 for the axisymmetric disk model, and 0.15 for the spherical shell and axisymmetric shell model.…”
Section: Kernel Of Intensitysupporting
confidence: 86%
“…matter from a non-degenerate star to reach the critical mass for SN explosion (Whelan & Iben 1973;Nomoto 1982), whereas in the double degenerate channel the explosion is achieved by the merging of the WD with a degenerate companion (Iben & Tutukov 1984;Webbink 1984). In either case, circumstellar material (CSM) may be ejected before the explosion and studies of which may provide unique clues to the nature of the progenitors of SNe Ia (Förster et al 2012;Shen et al 2013;Yang et al 2017;Li et al 2019;Ding et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, a few Ia SNe were observed to late times with a more complete spectral coverage, and were found to exhibit a late-time flattening of the light curve (Graur, et al 2016;Dimitriadis, et al 2017;Kerzendorf, et al 2017;Shappee, et al 2017;Yang, et al 2018;Graur, et al 2018a,b;Graur 2019;Li, et al 2019). Assuming that the observed flattening is due to heating by 57 Co and 55 Fe decays, and ignoring delayed deposition, abundances of 57 Co and 55 Fe were derived, typically assuming fully trapped positrons.…”
Section: Introductionmentioning
confidence: 99%
“…To date, this so-called "IR catastrophe" has not been observed in the optical. In fact, several recent studies have shown that the decline of the optical light curves begins to slow down at ∼ 800 days (Cappellaro et al 1997;Leloudas et al 2009;Fransson & Jerkstrand 2015;Graur et al 2016Graur et al , 2018bGraur 2019;Shappee et al 2017;Yang et al 2018;Dimitriadis et al 2017;Kerzendorf et al 2017;Li et al 2019). 2012ht, 2013dy, 2017erp, 2018gv, and 2019np in their host galaxies.…”
Section: Introductionmentioning
confidence: 99%